INFLUENCE OF COVID 19 ON INDONESIAN AND WORLD ECONOMY - Natallios Peter Sipasulta; Dionysia Kowanda; Aditya Rian Ramadhan (International Journal Multidisciplinary Science, 2022)
Covid 19 has become a very serious problem for many people wherever they are, both at home and abroad. This has been shown by the occurrence of various events that have shaken the governments of world countries where they have to overcome problems that arise both from within and from abroad. Covid 19 has become an important topic in the last 3 years since it was first detected in 2019 in the city of Wuhan, China. The death of humans in very large numbers and also in other countries due to contagion spread through people traveling from one country to another has made the problems caused by Covid 19 a formidable challenge for every country, where every The state must be able to regulate the travel process of its citizens entering and leaving the country, on the other hand the government must also regulate the process of accepting foreign nationals who will enter or leave a country. Taking into account these things, it can be observed that there is a significant influence and impact on the economy of a region or country that is affected by human movements, both between countries and those occurring within the country. The existence of movement restrictions to reduce the spread of the virus that occurs from human or person-to-person meetings has resulted in a decrease in the level or number of transactions that occurred during this period or since Covid 19 was detected in 2019 and even now the impact is still being felt until now.